KAJIAN DAYA TARIK HUTAN ADAT WONOSADI SEBAGAI OBYEK WISATA ALAM DI DAERAH ISTIMEWA YOGYAKARTA (Desa Beji, Kecamatan Ngawen,Kabupaten Gunungkidul) - , NUR WAHYUNI PURNAMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Every year the number of tourists in Yogyakarta Special Region has an increasing. There is an increasing number of tourists, so thatthe need for an alternative new attractions. Indigenous Forests Wonosadiis customforestthat only one inYogyakarta Special Region. One of the factors that tourists to visit the tourists area is anobject tourist attraction.Therefore, it becomes nessecary to know how significant Indigenous Forest Wonosadi as a tourist attraction and how significant the tourist attraction toward thesurrounding tourism object.. The study was aimed to evaluate the tourist attraction inIndigenous Forests Wonosadi. Data gathering was performed by analysis SBE(Scenict Beauty Estimation) to valuated the beauty, and the survey method with a questionnaire to valuated the uniqueness and value. The number of respondents on this research is 50 people. The respondents isclassified into 3 groups, that is government agencies, scientists and society. The analysis that is used to determine the quality of tourist attraction is scoring analysis (high quality, medium quality, low quality). Comparative analysis was conductedin descriptive way, by comparing the scores obtained from the variable calculation of tourist attraction (uniqueness, beauty and value). The result shows that the potency of Indigenous Forests Wonosadi has score on its beauty of 87.36 (beauty is of medium quality), score on its uniqueness of 384 (uniqeness is of high quality), and score on its value of 394.5 (high value). Based on these values, the potency of Indigenous Forests Wonosadi is categorized as a high tourist attraction with a score of 865.86. Compared to score of Gunung Api Purba tourist attraction(885.14). Tourist attraction Wonosadi is lower, but the tourist attraction category of high so that Indigenous Forests Wonosadican be developed into a tourist attraction.